Design and Build an Inventory Information System Using the Web-Based First-In First-Out (FIFO) Method at DNA Art Shop: Rancang Bangun Sistem Informasi Inventory Barang Menggunakan Metode First-In First-Out (FIFO) Berbasis Web Pada DNA Art Shop - Adi Duta Saputra P., I Gede; Dwi Nuryana, I Kadek (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
MSMEs (Micro, Small, and Medium Enterprises) have a very important role in a country's economy. One of the MSMEs engaged in tourism is DNA Art Shop, located in Tanah Lot Art Market, Tabanan, Bali. This UMKM sells various souvenirs and souvenir clothes for tourists visiting Tanah Lot. Of course, in running business operations, each MSME has its own obstacles. Based on information obtained during interviews with sellers from DNA Art Shop, the obstacles faced are related to the inventory of goods. This obstacle is caused by the process of recording incoming and outgoing goods that have not been recorded properly, excess and shortage of stock items due to errors in stock information, and the accumulation of old goods that have not been sold. In connection with these problems, the purpose of this study is to design an inventory information system that can overcome the obstacles of recording goods at DNA Art Shop. The design of this information system uses the Rapid Application Development (RAD) method which consists of Requirement Planning, Workshop Design, Implementation, and Testing. The inventory management method applied in this study is the First In First Out (FIFO) method where the first item to enter inventory is the first to be sold or used. The result of this research is a website-based inventory information system that is a solution to the problem of data collection of goods at DNA Art Shop.